Rehabilitation and bankruptcy in the legislative practiceof the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2016)
In this article the authors examine the nature of bankruptcy, its causes, dynamics of change in relation to the concept of bankruptcy in the de-velopment of the world economy. Historic legislative practice of foreign countries in the field of bankruptcy is given. The analysis of the institute of rehabilitation and bankruptcy in the Republic of Kazakhstan was made. It is noted that the institution of bankruptcy is a tool of improvement and development of the national economy, designed to protect the interests of employers and the state. Recent changes in the regulatory practice aimed at creating mechanisms of rehabilitation of insolvent enterprises. Raises issues of personal bankruptcies.
Keywords: bankruptcy; the institution of bankruptcy; rehabilitation; law; administrator; debtor; creditor; rehabilitation manager; bankruptcy individuals.